Construction of Drug User Identity at South Sulawesi BNNP Rehabilitation Center - Pitang, Silvester Edwin Surya; Idham Irwansyah Idrus; Ahmadin (CV. Inara, 2025)
This study aims to determine: 1) how the construction of drug user identity is formed and developed in rehabilitation centers 2) how the self-identity of drug users in the community 3) how the role of the environment on the self-identity of drug users. The type of research used is qualitative research with a descriptive approach. The number of informants consisted of 12 people, with the criteria namely: 1) clients who undergo outpatient treatment at BNNP South Sulawesi 2) counselors at BNNP South Sulawesi. Data collection techniques used were observation, documentation, and interviews. Data validity check is done by a member check. Data analysis is data condensation, data presentation, and conclusion. The results of the study found that the construction of the identity of drug users was strongly influenced by their environment, this research occurs that many clients who use drugs because of the incitement of friends and environmental influences and an important point that BNNP be the vanguard to make the clients recover productive and functioning socially in society